2013
DOI: 10.7150/ijms.5693
|View full text |Cite
|
Sign up to set email alerts
|

Lef1 Contributes to the Differentiation of Bulge Stem Cells by Nuclear Translocation and Cross-Talk with the Notch Signaling Pathway

Abstract: Lymphoid enhancer binding factor-1 (Lef1) is an essential regulatory protein in the Wnt signal pathway, which controls cell growth and differentiation. Investigators in the field of skin biology have confirmed that multipotent bulge stem cells (BSCs) are responsible for hair follicle development and regeneration. However, the role of Lef1 remains poorly understood. In this study, we investigated the pattern of Lef1 expression at different stages of the hair growth cycle. Lef1 was strongly expressed during anag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…The recent discovery made during a study of the mechanisms at the basis of the differentiation of bulge stem cells is intriguing. Indeed, it has been observed that LEF1 crosstalks with the Notch signaling pathway, as JAG1 is its downstream target [34]. This information is particularly relevant because it is known that JAG1 is more strongly expressed in APL than in other AML subtypes [35] and that it is rapidly downregulated by ATRA treatment of NB4 cells and primary APL blasts [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery made during a study of the mechanisms at the basis of the differentiation of bulge stem cells is intriguing. Indeed, it has been observed that LEF1 crosstalks with the Notch signaling pathway, as JAG1 is its downstream target [34]. This information is particularly relevant because it is known that JAG1 is more strongly expressed in APL than in other AML subtypes [35] and that it is rapidly downregulated by ATRA treatment of NB4 cells and primary APL blasts [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…β‐catenin is stored in the nuclei of anagen hDPCs and stimulates growth signals to activate hair follicle morphogenesis or growth. LEF‐1, one of the key mediators in the Wnt/β‐catenin pathway, plays an important role in regulating the interaction between the epidermis and dermis in hair follicles and is critical to the differentiation of bulge stem cells . For example, LEF‐1 overexpression in bulge stem cells increases β‐catenin translocation into the nucleus to activate target genes of the Wnt pathway, resulting in hair shaft precursor cell differentiation in the hair matrix .…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery made during a study of the mechanisms at the basis of the differentiation of bulge stem cells is intriguing. Indeed, it has been observed that LEF1 crosstalks with the Notch signaling pathway, as JAG1 is its downstream target [34]. This information is particularly relevant because it is known that JAG1 is more strongly expressed in APL than in other AML subtypes [35] and that it is rapidly downregulated by ATRA treatment of NB4 cells and primary APL blasts [36,37].…”
Section: Discussionmentioning
confidence: 99%